PERBEDAAN LATAR BELAKANG PENDIDIKAN DAN MASA KERJA GURU BIMBINGAN DAN KONSELING TERHADAP PELAKSANAAN LAYANAN BIMBINGAN DAN KONSELING FORMAT KLASIKAL - Isari, Vivi; Efendi, Z. Mawardi; Suhaili, Neviyarni (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2017)
This study is concerned with the presence of BK teachers who have no educational background in guidance and counseling. They are appointed by the principal because they are deemed to be and come from educational and non-educational graduates with little teaching hours. This certainly has an impact on the quality of the implementation of guidance and counseling services in schools. This study aims: (1) to reveal and describe the implementation of guidance and counseling services by BK teachers; (2) differences in the implementation of guidance and counseling services classical format reviewed from the background SI BK and Non BK; (3) differences in the implementation of classical guidance counseling and counseling services in terms of working period of <16 years and ? 16 years; (4) the interaction of education background and working period of BK teacher in providing guidance and counseling service of classical format. This research uses quantitative method with comparative descriptive approach. The subjects of the study were all BK teachers with BK and Non BK BK Sijunjung who numbered 32 people. The instruments used are Likert model scale with 0.965 realib and 0.507 validity (implementation of classical counseling guidance and counseling service). Data were analyzed by using variance analysis technique (ANOVA). The result of data analysis shows: 1) the implementation of guidance and counseling service of the classical format given by the teacher of education background S1 and Non BK with working period <16 years and ? 16 years are in high category, and the average score of implementation of guidance and counseling service of classical format same category. 2) there is no significant difference in the background of BK and Non BK S1 education. 3) there is no significant difference in the implementation of classical counseling guidance and counseling services in terms of working period of <16 years and ? 16 years. 4) there is no significant interaction between the education background score and the working period of the BK teacher towards the implementation of classical counseling guidance and counseling services.